Identifikasi Kepuasan Food Traveler Pada Rumah Makan Sari Rasa Kabupaten Ende (Studi Deskriptif Pada Website Tripadvisor) - Yulius Laga; Santy Permata Sari (ANALISIS, 2020)
This research is the result of a food traveler review on the Tripadvisor website from 2014 to 2020. The review was conducted at Sari Rasa Ende Regency, with 154 reviewers. The research method was carried out with Descriptive Statistics with SPSS 20 Analysis Tool. The results showed that the current condition of Sari Rasa Restaurant has become an icon for food travelers and tourists specifically to enjoy local food menus with distinctive flavors, the thing that needs to be maintained is hospitality services, including good communication and the authenticity of the local food menu, on the other hand need to be improved in the quality of taste that is tailored to the characteristics of tourists, the portion of food offered must also be adjusted to the pattern of visitor consumption, as well as the quality and atmosphere of the room and facilities that need to be improved.